Features of the reparative chondrogenesis course in induced joint cartilage defect and application of cartilage protector - Slesarenko N.A.; Borhunova E.N.; Shirokova E.O.; Ivantsov V.A.; Kuznetsov T. Yu. (E3S Web of Conferences, 2021)
The article reflects information on morphological features of joint cartilage in normal and at induced damage. In animals of the experimental group, the effect of “Stop Arthritis” preparation on the structural and functional cartilage state in the regenerative process dynamics was evaluated. The research was performed based on the Department of Anatomy and Histology of Animals named after Professor A.F. Klimov MSAVMIB — MVA named after K.I. Skryabin. Gonarthrosis modeling was performed on 13 clinically healthy rabbits of Chinchilla breed at the age of 5 months, on which surgical intervention was carried out to create a bilateral articular cartilage defect in the kneecap unit region by excising a fragment of articular cartilage to the subchondral bone. As a result of the studies it was revealed that spontaneous articular cartilage healing after a surgical trauma occurs with the participation of connective tissue pannus, which is obviously formed both on the side of the articular capsule and the subchondral bone. In this case, healing is accompanied by subchondral osteoporosis, as well as the development of deforming arthrosis in the kneecap block area. It was shown that the use of “Stop Arthritis” cartilage protector optimizes reparative chondro- and osteogenesis in damaged tissues of the knee joint, which is confirmed by the formation of a holistic articular coating with organ-specific zonal differentiation.